Traumatic Retroclival Subdural Hematoma - Tom Van der Stricht; Floris De Munck; Koenraad Nieboer (Journal of the Belgian Society of Radiology, 2023)
Teaching Point: Retroclival subdural hematoma is a rare type of extra-axial hematoma after craniocervical trauma.